2002
DOI: 10.1002/jbm.1281
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human bone morphogenetic protein‐2 promotes osteogenesis within atelopeptide type I collagen solution by combination with rat cultured marrow cells

Abstract: We evaluated the combination effect of recombinant human bone morphogenetic protein-2 (rhBMP-2) and cultured rat bone marrow mesenchymal stem cells (MSCs) in atelopeptide type I collagen (AC) solution on osteogenesis in a diffusion chamber (DC) to develop a bone substitute having consistent osteogenic capability for clinical applications. The cultured MSCs were obtained by 10-day primary culture of fresh bone marrow cells of Fischer rats. We prepared three groups of DCs: AC solution with rhBMP-2, AC solution w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…We also reported that BMP-2/collagen/MSCs in the diffusion chambers (DC) showed bone formation on the surface areas of the membrane filter and cartilage formation in the central areas of the DC. 17 Furthermore, it should be noted that the current HA ceramics we used were derived from coral, and the complete interpore connection resulted in an open-pore structure. The three-dimensional structure easily intro- duces neovascular invasion into the pore areas, and bone formation always accompanies the vasculature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also reported that BMP-2/collagen/MSCs in the diffusion chambers (DC) showed bone formation on the surface areas of the membrane filter and cartilage formation in the central areas of the DC. 17 Furthermore, it should be noted that the current HA ceramics we used were derived from coral, and the complete interpore connection resulted in an open-pore structure. The three-dimensional structure easily intro- duces neovascular invasion into the pore areas, and bone formation always accompanies the vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, collagen gel combined with BMP-2 and MSCs could be used as injectable and resorbable osteogenic materials. 17 Other resorbable materials available for this purpose include polyglycolic acid polymer and hydroxyapatite/collagen-poly-l-lactic acid composite. 32,33 In conclusion, when GDF-5 was used for making composite grafts in combination with porous materials and marrow MSCs, it was able to induce new bone formation without the appearance of cartilage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biopolymeric gels for immobilization of growth factors. Biopolymeric gels containing fibronectin, laminin, collagen, elastin or the glycosaminoglycans heparin sulphate, chondroitin sulphate, hyaluronic acid or a variety of synthetic hydrogels have been used as extracellular matrix-mimicking materials to immobilize growth factor-inducing moieties or growth factors directly [61,62]. For example, fibrin, which plays an important role in wound healing, has been used to link and deliver peptides or growth factors into the area of interest.…”
Section: Chemical Conjugation Of Growth Factors or Morphogens To Scafmentioning
confidence: 99%
“…Current studies mainly rely on the use of fresh autograft bone and various bone graft substitutes [Saito et al, 2001;Boo et al, 2002;Ikeuchi et al, 2002]. We believe that future strategies for the repair of bone defects could include the use of tissue engineering techniques that incorporate appropriate implants seeded with cells having an osteogenic potential.…”
Section: Introductionmentioning
confidence: 99%